Deposition and Wear of Deposits in Swirl Spray Driers: The Equilibrium Exchange Rate and the Wall-borne Residence Time. (2015) - Francia, Víctor; Martín, Luis; Bayly, Andrew E.; Simmons, Mark J.H.
Abstract: Wall deposits are omnipresent in many particle technology operations, such as spray drying and granulation processes. Their impact has been long recognized and is typically considered detrimental to the process performance. Counter-current spray drying units, such as those used in the manufacture of detergents, make use of strong swirling flows which leads to substantial multi-layered deposits at the walls. However their relation to the rest of the process has never been studied in detail. The work presented here discusses the generation of the structure at the walls and how it interacts with the air-borne population of particles. A tracer experiment is outlined that permits one to track the release of material from the deposits and differentiate the origin of aggregates in the product, as being generated either by the atomization or through the erosion of deposits. Monitoring of the wall and analysis of the release rate of the tracer has permitted identification of a dynamic equilibrium between the rates of deposition and re-entrainment, and quantification of the exchange rate above 12-20% of the full production. The age of the re-entrained material, indicative of the time the granules remain resident at the wall, appears much higher than expected for an air-borne trajectory. Such observations suggests that the description of the spray drying process exclusively in terms of the air-borne condition of particles is incomplete, at least in relation to the manufacture of detergents in swirl assisted systems. Focus should be paid to the wall-borne condition of the product, for it is seen to govern the generation of large granule sizes and dominate the residence time and drying kinetics of a significant part of the product.